2015
DOI: 10.3390/ijms160817535
|View full text |Cite
|
Sign up to set email alerts
|

Features in the Lipid Status of Two Generations of Fingerlings (0+) of Atlantic Salmon (Salmo salar L.) Inhabiting the Arenga River (Kola Peninsula)

Abstract: The present research focused on determining the lipid status of salmon fingerlings (0+) in early development after dispersal form groups of spawning nests in biotopes of different hydrological conditions. The revealed qualitative and quantitative differences in the levels of phospholipids and fatty acids among two generations of Atlantic salmon fingerlings (0+) living in different biotopes of the Arenga River (a tributary of the Varzuga River) may be associated with the peculiarities of their genetically deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
3
2
0
1
Order By: Relevance
“…Freshwater fish, compared with marine food-derived 18:3ω-3, more actively convert this molecule to long-chain PUFAs [ 2 , 20 ]. The 22:6ω-3/18:3ω-3 ratio, indicating the level of ω-3 PUFA metabolism, increased from 0.6 to 1.1 with age in the studied fish, suggesting that the increased amount of long-chain PUFAs in the juveniles at age 1+ might be associated with the start of fatty acid profile modification from a freshwater type to a marine type, consistent with the results of a previous study in fish aged 2+ and smolts (3+), inhabiting another biotopes of the Varzuga River [ 12 , 13 , 14 ]. Changes in the FA spectrum reflecting increasing PUFAs promote smoltification and the further migration of smolts to the sea [ 21 ].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Freshwater fish, compared with marine food-derived 18:3ω-3, more actively convert this molecule to long-chain PUFAs [ 2 , 20 ]. The 22:6ω-3/18:3ω-3 ratio, indicating the level of ω-3 PUFA metabolism, increased from 0.6 to 1.1 with age in the studied fish, suggesting that the increased amount of long-chain PUFAs in the juveniles at age 1+ might be associated with the start of fatty acid profile modification from a freshwater type to a marine type, consistent with the results of a previous study in fish aged 2+ and smolts (3+), inhabiting another biotopes of the Varzuga River [ 12 , 13 , 14 ]. Changes in the FA spectrum reflecting increasing PUFAs promote smoltification and the further migration of smolts to the sea [ 21 ].…”
Section: Discussionsupporting
confidence: 89%
“…The SFA/PUFA ratio decreased in salmon juveniles (from 0.98—fish at age 1+ to 0.78—fish at age 2+), reflecting increased levels of ω-3 PUFAs. We detected the same dynamic in a previous study on salmon juveniles (0 +, 1+, 2+, and 3+ smolts) from other biotopes of the Varzuga River (the Arenga tributary and the littoral of the Varzuga River) [ 14 ].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In this study, tilapia were raised under same exogenous conditions therefore culturing period and diet were the possible factors that could affect fatty acid profile of fish under study. From our findings, DHA, total n3 and n3/n6 ratio increased significantly (P<0.05) from month 1 to month 3 in both tissues (Table 6 and 7), an observation which relates with previous finding that fatty acid profile in fish is dependent on fish age (Parlov et al, 2009, Nemova et al, 2015aNemova et al, 2015b;Denis and Nina, 2016). A study on Atlantic salmon indicated that in two year feeding period, the levels of n3 fatty acids increased from 24 to 29.5%, DHA increased from 5.4 to 8.6% and n3/n6 ratio increased from 2.5 to 3 (Svetlana et al, 2003).…”
Section: Discussionsupporting
confidence: 74%